100,000 Expected at ConExpo-Con/Agg 2002 in Las Vegas (Society for Mining, Metallurgy & Exploration, 2002)
More than 100,000 people are expected to be in Las Vegas, NV in March for ConExpo-Con/Agg 2002, the largest exhibit of its kind in the Western Hemisphere. This triennial event features equipment, services and technical sessions geared toward the global construction aggregates and ready mix concrete industries. ConExpo-Con/Agg 2002 will take place March 19-25, 2002 at the Las Vegas Convention Center. For registration information, contact the show offices, phone 800-867-6060, 414-298-4141, or 301-587-3140, Website www.conexpoconagg.com.